Deteksi Mycobacteria pada Area Peternakan Unggas di Kabupaten Malang, Jawa Timur: Upaya Pendekatan One Health - Kurniawati, Siti; Ramadhani , Najma; Ayu Savitry , Diaz; Titah Pinasti , Roro; Jannah , Miftahul; Ivana Alexsandra Tasumo, Jessica; Gibraltar Makta , Averoes (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Mycobacteria represent a critical microbial agent with significant implications for animal and human health. Mycobacteria can be found in poultry farm environments, serving as a risk factor for transmission of infection. This study aims to determine the prevalence of Mycobacteria in poultry farming areas. Methods: A total of 25 environmental samples were systematically processed and analyzed using established diagnostic protocols. Mycobacteria identification employed standard microbiological cultivation techniques and acid-fast staining methods. Results The findings revealed an 8% prevalence of Mycobacteria among the examined samples. This prevalence rate demonstrates the bacterial presence within the poultry farming environment, indicating potential transmission risks for both animal and human populations. Conclusion The study successfully documented Mycobacteria presence in poultry farming environments, emphasizing the necessity for continued microbiological surveillance and comprehensive health risk assessments. Further research is recommended to elucidate the specific mechanisms of bacterial transmission and potential mitigation strategies. Keywords: Mycobacteria, Poultry Farm, Soil, Environmental Keywords : consists of, 3-5 terms, in English